2017
DOI: 10.20944/preprints201703.0190.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and Preliminarily Cytotoxicity to A549, HCT116 and MCF-7 Cell Lines of Thieno[2,3-d]pyrimidine Derivatives Containing Isoxazole Moiety

Abstract: Abstract:Under the guidance of our previous achievements, and in order to extend this small molecular library. In current work, other 21 novel structures of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The cytotoxicity data revealed that compound 184 (Figure 26; IC 50 : 18.87 ± 0.2 μg/ml) with chloro substitution on the phenyl ring displayed the highest cytotoxicity against the MCF‐7cell line, while the compound 185 (Figure 26; IC 50 : 40.74 ± 1.7 μg/ml) with unsubstituted phenyl ring showed the maximum cytotoxicity against HeLa cell line 231 . In 2018, Yong et al, 232 worked on the synthesis of thienopyrimidine containing the isoxazole template. They screened their anticancer efficacy taking gefitinib as a reference standard.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cytotoxicity data revealed that compound 184 (Figure 26; IC 50 : 18.87 ± 0.2 μg/ml) with chloro substitution on the phenyl ring displayed the highest cytotoxicity against the MCF‐7cell line, while the compound 185 (Figure 26; IC 50 : 40.74 ± 1.7 μg/ml) with unsubstituted phenyl ring showed the maximum cytotoxicity against HeLa cell line 231 . In 2018, Yong et al, 232 worked on the synthesis of thienopyrimidine containing the isoxazole template. They screened their anticancer efficacy taking gefitinib as a reference standard.…”
Section: Introductionmentioning
confidence: 97%
“…Amongst the analogs, compound 186 was found to show the maximum potency towards A549, HCT116, and MCF‐7 cell lines (Table 9). Thus, this molecule can be considered as a potential drug lead for the advancement of antitumor drugs 232 …”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, other heterocycles such as isoxazole derivatives were said to be powerful anticancer EGFR-TKIs. For example, the isoxazole derivative IV (Figure 1) was very good at inhibiting cancer cells proliferation, 15 and the isoxazole derivatives V were good at inhibiting cancer cells expressing EGFR-TK (Figure 1). 16 In the same way, 1,2,4-oxadiazole is the only oxadiazole that can be found in natural products.…”
Section: Introductionmentioning
confidence: 99%